Early complementary feeding and the incidence of stunting in toddlers - Ahdatul Islamiah; Nurun N. Aini Tallo (Jurnal Kesehatan Ibu dan Anak, 2020)
Data from the WHO in 2018 showed that babies received early complementary feeding as much as 69.8%. Most toddlers who received early complementary feeding had a 2.8 times risk of becoming stunted (Z score <-2). The purpose of this study was to identify the factors that influence the provision of early complementary foods with the incidence of stunting in toddlers. This research was quantitative research using Interential Statistics method through a Cross Sectional approach. The population was stunting toddlers who were given early complementary food in Lelamase Village, Bima City in 2020 as many as 35 toddlers, sampling using the Total Sampling technique. Analysis using Chi Square test for Bivariate Analysis and Logistic Regression analysis for Multivariate Analysis. The results show that the variables that influence early complementary feeding with stunting was maternal knowledge with p-value = 0.000, maternal health condition with p-value = 0.024, local culture with p-value = 0.025, complementary food advertising and promotion of formula milk with p- value = 0.037, support for health workers p-value = 0.025. While the factors that did not affect the provision of early complementary food with stunting were the mother's work factor, p-value = 0.068 and maternal age, p-value = 0.043. The dominant factor that influences the provision of early complementary feeding with the incidence of stunting is the mother's knowledge of 110 times for toddlers who have mothers with less knowledge than toddlers who have good mothers. The provision of early complementary food to stunted toddlers was influenced by lack of maternal knowledge, poor maternal health conditions, local culture, complementary food advertising and promotion of formula milk and lack of support from health workers and the most dominant factors was mother's knowledge.